Relationship of serum IL-6, C-reactive protein, erythrocyte sedimentation rate, and knee skin temperature after total knee arthroplasty: a prospective study - Honsawek, Sittisak (Springer-Verlag, 2010)
Knee osteoarthritis is a common cause of severe pain and functional limitation. Total knee arthroplasty is an effective procedure to relieve pain, restore knee function, and improve quality of life for patients with end stage knee arthritis. The aim of this study was to investigate the inflammatory process in patients with primary knee osteoarthritis before surgery and in subsequent periods following total knee arthroplasty. A prospective study of 49 patients undergoing primary total knee replacements was conducted. The patients were evaluated by monitoring serum interleukin-6 (IL-6), C-reactive protein (CRP), erythrocyte sedimentation rate (ESR), knee skin temperature, and clinical status. Measurements were carried out preoperatively and postoperatively on day one and at two, six, 14, and 26 weeks during follow-up review in the knee clinic. The serum IL-6 and CRP were elevated on the first postoperative day but fell to preoperative values at two weeks postoperatively. Both returned to within the normal range by six weeks postoperatively. In addition, the postoperative ESR showed a slow rise with a peak two weeks after surgery and returned to the preoperative level at 26 weeks postoperatively. The difference in skin temperature between operated and contralateral knees had a mean value of +4.5°C at two weeks. The mean value decreased to +3.5°C at six weeks, +2.5°C at 14 weeks, and +1.0°C at 26 weeks. The difference in skin temperature decreased gradually and eventually there was no statistically significant difference at 26 weeks after surgery. A sustained elevation in serum IL-6, CRP, ESR, and skin temperature must raise the concern of early complication and may suggest the development of postoperative complication such as haematoma and/or infection.